The treatment of the problem of privacy in Wittgenstein's later writings - Holiday, Bernard John (Department of Philosophy, 2016)
My attempt in this thesis will therefore be twofold. I shall try to outline the problem of the privacy of sensation as a special case of philosophical scepticism of our having knowledge of other minds. Certain ramifications of this question, particularly the problems of linguistic meaning, and intentional action will also be discussed. Secondly I shall try, in discussing Wittgenstein's treatment of this problem, to show that his technique is a satisfactory one, not only for "curing" this problem, but for handling all philosophic problems. In other words the unity of Wittgenstein's philosophy will be stressed. This unity is not the one which is receiving a great deal of attention at the moment, viz. the unity of the Tractatus and the later.works. But I refer rather to the fittedness of Wittgenstein's philosophical activity to his domain of interest - conceptual investigations. In these investigations he discovers no new fact, gives no new piece of information. What he does is to practice philosophy in a new way and initiate us into a new form of activity. In this, it seems to me, his work is supremely original and greatly valuable.